2017
DOI: 10.1007/s11010-017-2944-x
|View full text |Cite|
|
Sign up to set email alerts
|

Isorhamnetin protects against cardiac hypertrophy through blocking PI3K–AKT pathway

Abstract: Isorhamnetin, a flavonoid compound extracted from the Chinese herb Hippophae rhamnoides L., is well known for its anti-inflammatory, anti-oxidative, anti-adipogenic, anti-proliferative, and anti-tumor activities. However, the role of isorhamnetin in cardiac hypertrophy has not been reported. The aims of the present study were to find whether isorhamnetin could alleviate cardiac hypertrophy and to define the underlying molecular mechanisms. Here, we investigated the effects of isorhamnetin (100 mg/kg/day) on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…In the compound-target network, some key 0 -23 33 33 33 33 33 33 33 33 33 33 33 33 33 33 33 - [26]. Moreover, quercetin and isorhamnetin can inhibit the PI3K/AKT signaling pathway activation to protect heart from cardiac hypertrophy and HF [27,28]. Study shows that calycosin and formononetin inhibit the activation of the renin-angiotensin-aldosterone system to improve the symptoms of HF [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the compound-target network, some key 0 -23 33 33 33 33 33 33 33 33 33 33 33 33 33 33 33 - [26]. Moreover, quercetin and isorhamnetin can inhibit the PI3K/AKT signaling pathway activation to protect heart from cardiac hypertrophy and HF [27,28]. Study shows that calycosin and formononetin inhibit the activation of the renin-angiotensin-aldosterone system to improve the symptoms of HF [29].…”
Section: Discussionmentioning
confidence: 99%
“…Taxifolin, one of quercetin derivatives, has the ability to blunt cardiac fibrosis induced by pressure overload, the mechanism underlying anti-fibrotic effect of taxifolin dependents on inhibition of TGF-β/Smad signaling pathway (Guo et al, 2015 ). Isorhamnetin, another ingredient of flavonols, ameliorates cardiac hypertrophy and fibrosis induced by aortic banding (Gao et al, 2017 ). Consistent with the results above, Boerhavia diffusa extracted with ethanol (BDE) is a rich source of bioactive flavonols containing quercetin, boeravinone, kaempferol, and caffeic acid, mitigating Ang II-induced cardiac fibrosis via the inhibition of TGF-β1 expression and collagen deposition (Prathapan et al, 2017 ).…”
Section: Anti-fibrotic Effect Of Polyphenols On Cardiac Fibrosismentioning
confidence: 99%
“…Isorhamnetin (Isor; molecular formula, C 16 H 12 O 7 ), a flavonol aglycone isolated from the plant Hippophae rhamnoides L, is frequently used in traditional Chinese medicine to prevent and treat various diseases. Isor has been demonstrated to exert a variety of effects, including antioxidant, anti-inflammatory, antitumor, antiviral, anti-ERS and neurodegenerative injury protection effects ( 20 , 21 ). Recent research has revealed that Isor attenuates liver fibrosis by inhibiting transforming growth factor (TGF)β/SMAD signaling and relieving oxidative stress ( 22 ).…”
Section: Introductionmentioning
confidence: 99%